The Effect Of Parental Involvement And Social Support On Career Decision-Making - Alaydrus, Syarifah Nabila; Rahman, Nadya Novia (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Students are expected to know the career goals they want to achieve and be able to choose a career that they are interested in from the start. In reality, there are still many students who experience doubts when they want to decide on the career they want. This research adopted a quantitative approach with a research population of 90 FISIP University X students who were specifically selected through a purposive sampling technique. Statistical analysis of the data used a multiple linear regression model with the help of the SPSS computer program. The results obtained: (1) there is a significant influence of parental involvement and social support on career decision making with calculated F value = 6.358 F table = 3.10 and p value = 0.003 and has an influence contribution (R2) of 12.8%; (2) there is no significant positive influence of parental involvement on career decision making with beta coefficient (β) = 0.085, t = 0.727 t table = 1.987, and p value = 0.469 (p 0.05); (3) there is a significant positive influence of social support on career decision making with a beta coefficient value (β) = 0.306, t = 2.616 t table = 1.987, and p value = 0.010 (p 0.05).